"Terk ert frerm me - ze bermbe is quert serf" [Francois Mitterrand] - Pryor, Geoff, 1944- (1985)
French President Francois Mitterand invites Prime Minister Bob Hawke to visit the French nuclear testing site at Mururoa Atoll to show him how safe it is. Hawke declines the offer. The whole business of French testing in the Pacific provides the cartoonist with a golden opportunity to reprise the Peter Sellars Inspector Clouseau character from the Pink Panther movies.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 17 September 1985.
Part of the Pryor collection of cartoons and drawings.
With amicus no. 23378332.
Also available online
Keywords: Mitterrand, François, -- 1916-1996 -- Caricatures and cartoons; Presidents -- France -- Caricatures and cartoons; Inspector Jacques Clouseau (Fictitious character) -- Caricatures and cartoons; France -- Politics and government -- Caricatures and cartoons; Politicians